Czech Republic : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper reviews the fiscal reform of the Czech Republic, its key reform measures, and structural implications. The study also focuses on key challenges and demographic pressures facing the Czech economy, and describes the analytical framework of Global Fiscal Model (GFM) with technical details. It analyzes tax and expenditure measures and implications of additional measures for fiscal consolidation on debt sustainability. It reviews the formulation of the Czech National Bank (CNB) and also the Global Integrated Monetary and Fiscal Model (GIMF) to analyze monetary policy challenges lying ahead and the targets for reducing inflation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet